The Role of Cognitive Style in Academic Achievements and Creative Thinking among Students - Chakraborty, Joydeep; Das, Rajib; Kumar Jha, Kaushal (Indian Journal of Extension Education, 2025)
Cognitive ability significantly influences an individual’s life trajectory. The study explored the cognitive styles of undergraduate students in the Sadar sub-division of West Tripura district, Tripura, during 2024-25. A stratified random sample of 100 students was selected for the investigation. The study addressed specific research objectives and hypotheses related to gender based variations in cognitive style and its connection with academic achievement and creative thinking. Comparison of academic achievement scores between students with systematic and intuitive cognitive styles yielded a significant difference (t = 2.51, p < 0.05), favouring those with a systematic style. Pearson correlation analysis revealed strong positive and significant relationships between academic performance and both systematic (r = 0.86, tr = 16.68) and intuitive (r = 0.70, tr = 13.57) cognitive styles. In particular, students with a systematic cognitive style tended to perform better academically than those with an intuitive style. Further, students with a systematic cognitive style consistently secured higher academic scores compared to their intuitive counterparts. The findings contribute to the broader understanding of cognitive styles in educational settings and provide insights for enhancing academic support strategies in higher education.
Keywords: Cognitive style; Academic achievement; Creative thinking; College students; Tripura